Genotoxic studies of selected plant oil extracts on Rhyzopertha dominica (Coleoptera: Bostrichidae) - Sameer H. Qari; Nilly A.H. Abdel-Fattah (Journal of Taibah University for Science, 2017)
This study was conducted to compare the genotoxic effects of various concentrations of plant oils from Eruca sativa (Brassicaceae), Zingiber officinale (Zingiberaceae) and Origanum majorana (Lamiaceae) to the conventional organophosphate insecticide (Chlorpyrifos) against Rhyzopertha dominica Fabricius. The R. dominica population was reared for several generations without exposure to any insecticide. Wheat grains were sterilized at 55 °C for 6 h in order to eliminate any hidden infestation, treated with serial dilutions of Chlorpyrifos and plant oil extracts, and subsequently fed to R. dominica for 1, 2, 3, 6 and 8 days. The results indicated that the LC50 values of oils from E. sativa, Z. officinale and O. Majorana were 0.14, 0.23 and 0.32%, respectively, after 2 days. Genetic variations in DNA fragments after treatment with LC50 and LC25 concentrations of E. sativa, Z. officinale and O. majorana were detected by RAPD-PCR analysis using five primers. The results exhibited distinct DNA polymorphisms or alterations in DNA bands. These alterations varied depending on the substance being examined. Chlorpyrifos causes the highest level of DNA alterations (based on the appearance and disappearance DNA bands) followed by E. sativa, Z. officinale and O. majorana. These results were in direct correlation with the differences in mortality rates between extracts. It could be concluded that the plant oil extracts can be used as one of the integrated pest management tools to control R. dominica in stored products, as they are safer than chemical insecticides.